2019
DOI: 10.1038/s41467-019-09816-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal localization of immune transcripts defines hallmarks and diversity in the tuberculosis granuloma

Abstract: Granulomas are the pathological hallmark of tuberculosis (TB) and the niche where bacilli can grow and disseminate or the immunological microenvironment in which host cells interact to prevent bacterial dissemination. Here we show 34 immune transcripts align to the morphology of lung sections from Mycobacterium tuberculosis -infected mice at cellular resolution. Colocalizing transcript networks at <10 μm in C57BL/6 mouse granulomas increase complexity with time after infection. B-cell cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 60 publications
5
59
0
Order By: Relevance
“…As discussed above, intestinal epithelial cell RNA localization helps regulate local protein production along the apicobasal axis 61 (Figure 2C). Consequences of disrupting RNA localization in these cell types may underlie disease states such as inflammatory bowel disease, maldigestion or local immune responses 162, 163 …”
Section: Clinical Relevancementioning
confidence: 99%
“…As discussed above, intestinal epithelial cell RNA localization helps regulate local protein production along the apicobasal axis 61 (Figure 2C). Consequences of disrupting RNA localization in these cell types may underlie disease states such as inflammatory bowel disease, maldigestion or local immune responses 162, 163 …”
Section: Clinical Relevancementioning
confidence: 99%
“…In fact, multiplexed in situ imaging of cytokine and immune effector transcripts in TB infected Kramnik mice showed that cellular granulomas displayed networks, like CD68 -iNOS (inducible nitric oxide synthase) and IFNG (gamma interferon), associated with a robust response against M. tuberculosis [ 95 ]. This is in stark contrast to enriched transcript signatures found in necrotic granulomas, such as IL10 and FOXP3 , which are associated with immunosuppression [95] . Additional studies using the Kramnik model should consider mapping immune transcripts in multiple granulomas that are responsive and refractory to PZA treatment.…”
Section: Pza and The Host Environmentmentioning
confidence: 99%
“…All code is written in MATLAB and is freely available at (https://github.com/Moldia). Many steps follow previous publications 20,21,29,30 .…”
Section: Imagingmentioning
confidence: 99%